2008
DOI: 10.1145/1453775.1453787
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interrupt handling timeliness in real-time Linux operating systems

Abstract: Several real-time Linux extensions are available nowadays. Two of those extensions that have received special attention recently are Preempt-RT and Xenomai. This paper evaluates to what extent they provide deterministic guarantees when reacting to external events, an essential characteristic when it comes to real-time systems. For this, we define two simple experimental approaches. Our results indicate that Preempt-RT is more prone to temporal variations than Xenomai when the system is subject to overload scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…This delay depends on many factors such as number of CPU cores, CPU speed, CPU frequency scaling etc. No measurements have been done for this delay in this study, however, in [13], it has been shown that jitter in interrupt handling delay is 300 ns. This delay increases with CPU load and the maximum interrupt delay can be as high 70 μs.…”
Section: Software Timestamping Accuracymentioning
confidence: 83%
“…This delay depends on many factors such as number of CPU cores, CPU speed, CPU frequency scaling etc. No measurements have been done for this delay in this study, however, in [13], it has been shown that jitter in interrupt handling delay is 300 ns. This delay increases with CPU load and the maximum interrupt delay can be as high 70 μs.…”
Section: Software Timestamping Accuracymentioning
confidence: 83%
“…A reasonable tradeoff for many situations that does not require any special h/w support is obtained by taking time stamps in software as close as possible to the interrupt handler. A detailed analysis of the sources of uncertainty for software time stamps is provided in [18], and an accurate analysis of interrupt latencies can be found in [19].…”
Section: Measurement Of Clock Deviationsmentioning
confidence: 99%
“…In order to address this problem, some systems include additional mechanisms to set a bound on the number of the interrupts during certain time intervals [Regnier et al 2008]. However, it is clear that these mechanisms introduce an additional overhead.…”
Section: Decrease In the Utilization Bound In The Traditional Modelmentioning
confidence: 99%
“…Recently, there has been some research work on interrupt handling in the context of Linux for real-time [Regnier et al 2008]. Abeni et al [2009] present a reservationbased approach using interrupts as threads.…”
Section: Related Workmentioning
confidence: 99%